Diagnostic performance of MRI and histology in assessment of deep lipomatous tumours. Issue 13 (10th September 2019) - Cairncross, L.; Snow, H. A.; Strauss, D. C.; Smith, M. J. F.; Sjokvist, O.; Messiou, C.; Thway, K.; Hayes, A. J.
Abstract : Background: Deep lipomatous tumours can be benign lipomas or intermediate/locally recurring atypical lipomatous tumours (ALTs). Differentiating between these two entities clinically and radiologically is difficult. The aims of this study were to report a series of deep lipomatous tumours, comparing the clinical, radiological and pathological features of ALTs and lipomas; and to predict the likelihood of a lipomatous tumour being ALT based on anatomical site and MRI characteristics. Methods: This was a retrospective review of patients with deep lipomatous tumours presenting over 6 years to a tertiary sarcoma centre, with preoperative MRI, and preoperative or postoperative histology including MDM2 gene analysis. Sensitivity, specificity, predictive values and accuracy in diagnosing ALT were calculated for MRI and histopathological features. Results: Some 248 patients were included; 81 (32·7 per cent) had a final diagnosis of ALT. ALTs were larger than lipomas (median 19 versus 10 cm; P  < 0·001); there was no ALT smaller than 5 cm. A tumour presenting in the lower limb was more likely to be an ALT than a lesion at any other site (48·4 versus 13·5 per cent; P  < 0·001). In patients with lipomatous tumours at sites other than the lower limbs, MRI had a negative predictive value of 95 per cent for excluding ALT. Conclusion: Despite concern, most deep lipomatous tumours (nearly 70 per cent) are benign lipomas. Certain features imply that tumours are almost never ALT: smaller than 5 cm or located outside the lower limb with no suspicious characteristics on MRI. Tumours with these features might safely and confidently be managed outside tertiary sarcoma centres. Abstract : The distinction between deep lipomas and atypical lipomatous tumours (ALTs) can be difficult, and results in large numbers of referrals to tertiary sarcoma centres. This study showed that the majority of these tumours are benign and that certain features (size smaller than 5 cm, location outside the lower limbs) represent far lower‐risk groups, especially when preoperative MRI identifies no suspicious features. STIR, short tau inversion recovery. Useful guide to referral Abstract : Antecedentes: Los tumores lipomatosos profundos pueden ser lipomas benignos o tumores lipomatosos atípicos ( atypical lipomatous tumour, ALT) con potencial de recidiva local/intermedia. Diferenciar estas dos entidades desde el punto de vista clínico es difícil. Los objetivos de este estudio fueron presentar una gran serie de tumores lipomatosos profundos, comparando las características clínicas, radiológicas y patológicas de los ALT y de los lipomas y predecir la probabilidad de que un tumor lipomatoso sea ALT según su localización anatómica y las características de la RNM. Métodos: Revisión retrospectiva de pacientes con tumores lipomatosos profundos tratados en un centro terciario de sarcoma durante un período de 6 años, en los que se dispusiese de RNM preoperatoria y análisis MDM2 en el preoperatorio o postoperatorio. Se calculó la sensibilidad, la especificidad, el valor predictivo y la precisión diagnóstica de la RNM y de las características histopatológicas para el diagnóstico de ALT. Resultados: Se incluyeron 248 pacientes, de los que en solo 81 (32, 7%) se estableció un diagnóstico final de ALT. Los ALT fueron más grandes que los lipomas (19 versus 10 cm, P < 0, 001) y no hubo ningún ALT de tamaño menor de 5 cm. Hubo una mayor probabilidad de que un tumor fuera ALT si se presentaba en las extremidades inferiores en comparación con cualquier otra localización (48, 4% versus 13, 5%, P < 0, 001). En pacientes con tumores lipomatosos localizados en otros lugares que no fueran las extremidades inferiores, la RMN tuvo un valor predictivo negativo del 95, 5% para excluir la ALT. Conclusión: A pesar del recelo tradicional, la mayoría (70%) de los tumores lipomatosos profundos son lipomas benignos. Algunas características, como los tumores de menos de 5 cm y aquellos ubicados fuera de las extremidades inferiores sin características sospechosas por RNM, indican que los tumores casi nunca son ALT. Los tumores con esas características pueden tratarse de manera segura y con solvencia fuera de los centros de sarcomas terciarios. En casos seleccionados, puede ser útil la prueba genética MDM2 en la biopsia.